Identification of changes in volatile compounds in dry-cured fish during storage using HS-GC-IMS. (November 2020) - Zhang, Qi; Ding, Yicheng; Gu, Saiqi; Zhu, Shichen; Zhou, Xuxia; Ding, Yuting
Graphical abstract: Highlights: Twenty-two volatile components from dry-cured fish were identified by HS-GC-IMS. Aldehydes and esters gradually increased with the extension of storage time. Higher storage temperature increased the levels of aldehydes and alcohols. Butyl methyl ketone was a potential spoilage indicator of fish stored at 25 ℃. PCA distinguished samples in relation to storage temperature and time. Abstract: Changes in the volatile components of dry-cured fish during storage at 4 ℃ and 25 ℃ were investigated by HS-GC-IMS fingerprinting combined with principal component analysis (PCA). Topographic plots were used to establish the fingerprints of flavor substances, and 32 signal peaks were identified that corresponded to 22 compounds, mainly aldehydes, ketones, alcohols and esters. During storage at 4 ℃, 3-methylbutanal, dimethyl ketone and hexanal were the main volatile components, while hexanal, 1-octen-3-ol and 3-methylbutanal were the main compounds of dry-cured fish stored at 25 ℃; butyl methyl ketone was only observed at 25 °C. In the early stage of storage, significant changes in octanal, 3-methylbutanal and ethyl acetate were found in dry-cured fish at both temperatures (P < 0.05) while heptanal, pentanal and butanal changed significantly in the late stage (P < 0.05). PCA clearly distinguished the samples in relation to their storage temperature and time. In addition, heat map clustering analysis further revealed the differences and similarities among different samples, and those results were in accordance with the PCA results.